Olimpiade Rekording Dan Kontes Ternak Bibit Kambing Hasil Inseminasi Buatan Kelompok Peternak Kambing Wilayah Jawa Timur - Adelina Ari Hamiyanti (Journal of Innovation and Applied Technology, 2018)
Genetically the growth of local goat decrease each year. One of the factors that influences the productivity of goat in local breeders was the low of reproduction performance.  The objective of this project was to gain the qualified goat genetically with high goats productivity and reproduction in order to increase the breeders income.  The method of this study were plot demonstration, training and goat contest.  The result of this project could be seen from the decreasing of kidding interval became 8 month.  It was support by the development of recording system, oestrus detection and improvement of feed.  The quality of goat also increase with AI.  Overall the project run well in both partners and the breeders knew about the cheapest and efficiently of oestrus sychronisasion system, artificial insemination with frozen semen of Boer goat became more popular and the breeders more interest in, recording system could be applied easily and the availability of superior quality cross Boer goat from the contest result.